PEMBELAJARAN JARAK JAUH DI SMA TERBUKA KEPANJEN DENGAN MODEL PEMBELAJARAN DOMINAN ONLINE (DOMON) DINTACE LEARNING IN OPEN KEPANJEN HIGH SCHOOL WITH ONLINE DOMINATION LEARNING MODELS (DOMON) (Jurnal Teknodik, 2018)
Abstract:SMA Terbuka Kepanjen is a distace learning program that was initiated by Directorate of PKLK Ministry of Education and Culture of Indonesia. SMA Terbuka Kepanjen has set the quality objectives to be achieved, among them is to produce quality graduates through digital literacy. To achieve the target, one of the programs that is proclaimed is Academic System Strengthening Program and student with the target of the Availability of Elementary Facility of Sekolah Terbuka Kepanjen through www.elearning.smatjjkepanjen.sch.id page.LMS (Learning Management System) developed rapidly along with the advancement of ICT (Information and Communication Technology) in the form of Electronic Learning System or e-Learning System. E-Learning is an educational system that uses electronic applications to support the development of teaching and learning activities with computer network media, both intranet and internet. With e-Learning allows the process of education without going through direct face to face and the development of science to students can be done continuously. The implemented e-Learning model is the online dominant, or learning method that combines the 80% e-Learning system with the conventional or face-to-face method of 20%.Keywords: e-Learning, Learning Managements System, Dominant Online (domon) Abstrak:SMA Terbuka Kepanjen merupakan sekolah program jarak jauh yang dirintis oleh direktorat PKLK Kementerian pendidikan dan Kebudayaan RI. SMA Terbuka Kepanjen telah menetapkan sasaran mutu yang ingin dicapai di antaranya adalah menghasilkan lulusan yang berkualitas melalui literasi digital. Untuk mencapai sasaran tersebut, salah satu program yang dicanangkan adalah Program Penguatan Sistem Akademik dan kesiswaan dengan sasaran Tersedianya Fasilitas elearning SMA Terbuka Kepanjen melalui laman www.elearning.smatjjkepanjen.sch.id.LMS (Learning Management System)  berkembang pesat seiring kemajuan TIK (Teknologi Informasi dan Komunikasi) dalam bentuk Sistem Pembelajaran Secara Elektronik atau  e-Learning System. E-Learning adalah sistem pendidikan yang menggunakan aplikasi elektronik untuk mendukung pengembangan kegiatan belajar mengajar dengan media jaringan komputer, baik intranet maupun internet. Dengan e-Learning memungkinkan terjadinya proses pendidikan tanpa melalui tatap muka langsung dan pengembangan ilmu pengetahuan kepada mahasiswa bisa dilakukan secara terus menerus.  Model e-Learning yang diimplementasikan adalah dominan online, atau metode   pembelajaran yang menggabungkan antara sistem e-Learning 80 % dengan metode konvensional atau tata muka (face-toface) 20%. Kata Kunci: e-Learning, Learning Managements System,Dominan Online (domon)